Pozarządowy sektor niekomercyjny w Rosji w latach 2000–2018 : osobliwości funkcjonowania - Jach, Anna (Księgarnia Akademicka Publishing, 2019)
THE NON-GOVERNMENTAL, NON-COMMERCIAL SECTOR IN RUSSIA IN 2000–2018: PECULIARITIES OF FUNCTIONING The main scientific objective of the study was to present the specificity of Russian non-governmental, non-commercial sector as a phenomenon of trialistic provenance in the context of a state undergoing the process of transformation without a clearly defined vector. On the basis of factors characteristic of the non-governmental, non-commercial sector such as 1. the role they can play, 2. the involvement of Russian citizens in the activities of non-governmental, non-commercial organizations, 3. the three-sector sustainable model of a modern state, 4. expectations of different structures towards the tasks that both sides – the governmental and non-governmental one – should fulfil, 5. the role of an individual in the process of shaping or functioning of civil society, 6. typology of organizational and legal forms of non-governmental organizations, it can be stated that its functioning displays particular properties, which made it possible to present a collection of peculiarities of the functioning of the non-governmental, non-commercial sector in the years 2000–2018.